The Neural Secrets of Narration (ENTHYMEMA, 2023)
The Default Mode Network (DMN) is a network of brain regions responsible for active or passive narration and the sharing of experiences. The ability to simulate experiences and use memories to construct hypothetical tales about how people might behave is a fundamental skill in building a social aggregate as it allows us to foreshadow the consequences of our actions and reflect on the intentions of others, simulating their experiences to anticipate their behavior. We can process imaginary situations whose accuracy is a measure of our social skills since the closer the imagination approaches social reality, the better we negotiate our social worlds. The DMN is responsible for these activities that encompass the frontal and parietal structures of the brain along the midline, the lateral and medial temporal lobes, and the lateral parietal cortex. This work reviews the DMN in all its aspects, both in the construction of narrative plots and in the preparation of believable and immersive emotional scenarios, including endocrine outcomes (oxytocin and cortisol).
Keywords: Default Mode Network; Endocrinology; Emplotment; Mind reading; Social brain; Salience.